Bioactive compounds and pharmacological and food applications of Syzygium cumini – a review. Issue 12 (31st October 2018) - Chhikara, Navnidhi; Kaur, Ravinder; Jaglan, Sundeep; Sharma, Paras; Gat, Yogesh; Panghal, Anil
Abstract : The present review explores the nutritional, phytochemical and pharmacological potential as well as diverse food usages of Syzygium cumini . Abstract : The present review explores the nutritional, phytochemical and pharmacological potential as well as diverse food usages of Syzygium cumini . S. cumini is a traditional medicinal plant with various bioactive compounds distributed in all parts of the plant. The major bioactive compounds present in the edible part are myricetin, oxalic acid, gallic acid, citronellol, cyanidin diglucoside, hotrienol, phytosterols, flavonoids, carotenoids and polyphenols as well as micronutrients, accounting for numerous health benefits. The potential benefits of these bioactive compounds are to prevent/reduce metabolic abnormalities and various diseases. The health protective effects and functional properties of the plant were proved by different in vitro and in vivo pharmacological studies. All parts of the plant have good health benefits like hypoglycemic, anti-inflammatory, antianemic, antibacterial, antioxidant, antiallergic, hepatoprotective, hypolipidemic and antipyretic properties. The fruit of S. cumini can be consumed raw or processed in the form of jam, jellies, wine, fermented beverages and many other value added food products.